Purwarupa Alat Deteksi Ketinggian Banjir Perbantuan SMS Gateway Dan Mikrontroler - Ardi, Muhammad (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
Flood disasters still occur regularly and continuously in Indonesia. Flooding can occur due to the volume of water in the river beyond the river body. Many impacts caused by flooding, not only material losses, flooding can also cause loss of life. The impact of flooding can be reduced if people are better prepared to face the flood. One way is to quickly disseminate information on river water levels to the community. It is necessary to make a solution on how to design an automatic sluice using Arduino UNO R3 and how to monitor the water situation during floods. The working principle of this tool uses an ultrasonic sensor as a water level detector, Arduino as a data processor, servo motor as opening and closing the door bar automatically and the modem as an SMS notification. Because design based detection system is needed In this study there are two formulations of the problem (i) How to design flood altitude detection devices using Arduino uno r3 which can open and close automatically. (ii) How to test the flood altitude detection system using a wavecome modem. The research objective is divided into two parts (i) Creating a series of flood elevation devices using Arduino r3 so that it can open and close automatically (ii) Gets the results of flood elevation system testing with an sms gateway